Role of Computed Tomography Scan in Non-Localized Headache in Tertiary Hospital of Mid Western Region of Nepal - Ghimire, Prasanna; Singh, B. P.; Chaturvedi, S. K. (Journal of Nepalgunj Medical College, 2017)
Objective: To investigate the implication of a computed tomography scan for headache with non-localizing sign. Materials and methods: One hundred and thirty six patients with headache having non-localizing signs were included in this prospective study. Patients with age > 11 years, incomplete radiological or clinical data, recent/new onset headache, any immunosuppressive state, neurological deficits at the time of presentation, history of fever, trauma, any previous surgical intervention and any malignancy were excluded from the study. Results: Among the 136 patients, 73% were females and 27% were males with age range of 11- 76 years. Negative computed tomography scan was present in 91 (66.9 %) cases. Positive findings that significantly influenced the management were present in only 6 (4.4%) cases. Conclusion: Computed tomography in headache with non-localizing signs has a poor yield for a significant intracranial pathology. A careful and detailed assessment curtails the need for inadvertent imaging thus reducing the economic burden and health related hazards. Journal of Nepalgunj Medical College Vol.13(1) 2015: 2-4